2007
DOI: 10.1159/000111879
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiotensin II Receptor-1 Blockade in the Hypoxic Pulmonary Vasoconstriction Response in Newborn Piglets

Abstract: Background: Angiotensin-converting enzyme activity is increased in newborn infants with respiratory distress syndrome and in animals with alveolar hypoxia. Objective: To test whether angiotensin II (Ang II) mediates the pulmonary vasoconstriction induced by acute hypoxia in newborn piglets. Methods: Eight unanesthetized chronically instrumented newborn piglets (mean ± SEM; age 6.6 ± 0.6 days; weight 2,181 ± 174 g) were randomly assigned to receive a saline solution or the Ang II type 1 receptor (AT1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Although an initial study in isolated rat lungs perfused with physiological salt solution concluded that enhancement of HPV by ANG II was specific for both HPV and ANG II (152), this was not confirmed by a subsequent study in the same preparation, which found that increases in normoxic pulmonary vasomotor tone, whether caused by ANG II or other interventions, enhanced vasoconstrictor responses to both hypoxia and KCl (1240). Antagonists of ACE or ANG II receptors did not prevent HPV in dogs (720,823,997), cats (1552), or isolated rat lungs (509, 1242), but attenuated HPV in humans (259, 958) and neonatal piglets (249). Although the explanation for these discrepancies is unknown, the data suggest that ANG II may sometimes facilitate HPV.…”
Section: Angiotensin IImentioning
confidence: 90%
“…Although an initial study in isolated rat lungs perfused with physiological salt solution concluded that enhancement of HPV by ANG II was specific for both HPV and ANG II (152), this was not confirmed by a subsequent study in the same preparation, which found that increases in normoxic pulmonary vasomotor tone, whether caused by ANG II or other interventions, enhanced vasoconstrictor responses to both hypoxia and KCl (1240). Antagonists of ACE or ANG II receptors did not prevent HPV in dogs (720,823,997), cats (1552), or isolated rat lungs (509, 1242), but attenuated HPV in humans (259, 958) and neonatal piglets (249). Although the explanation for these discrepancies is unknown, the data suggest that ANG II may sometimes facilitate HPV.…”
Section: Angiotensin IImentioning
confidence: 90%
“…), but attenuated in piglets (Camelo et al . ). In addition, studies in chronically hypoxic rats provide evidence that angiotensin II may also contribute to the development of hypoxic pulmonary arterial remodelling and PH (Zakheim et al .…”
Section: Other Potential Modulators Of Hypoxic Pulmonary Vasoconstricmentioning
confidence: 97%
“…These observations were confirmed in adult humans when the RAS was not previously activated by dehydration or sodium depletion (23). In addition, we have demonstrated that pulmonary vasoconstriction induced by acute hypoxia in newborn piglets was significantly attenuated by the AT 1 -R blocker losartan (2). …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action of Ang II involve binding to AT 1 -R, as demonstrated in different studies reporting attenuation of pulmonary hypertension by AT 1 -R blockers and transient up-regulation of AT 1 -R in adult rats exposed to chronic hypoxia (6,7). Moreover, we have demonstrated that pulmonary vasoconstriction induced by acute hypoxia was significantly attenuated by the AT 1 -R blocker losartan in piglets (2). Therefore, it is possible that the RAS participates in the mechanisms leading to pulmonary hypertension induced by chronic hypoxia (4,5).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation